Health measurement scales : a practical guide to their development and use - Streiner, David L.; Norman, Geoffrey R. (Oxford University Press, 2008)
Clinicians and those in health sciences are frequently called upon to measure subjective states such as attitudes, feelings, quality of life, educational achievement and aptitude, and learning style in their patients. This fourth edition of Health Measurement Scales enables these groups who often have limited knowledge of statistics, to both develop scales to measure non-tangible health outcomes, and better evaluate and differentiate between existing tools. It covers how the individual items are developed; various biases that can affect responses (eg social desirability, yea-saying, framing); various response options; how to select the best items in the set; how to combine them into a scale; and then how to determine the reliability and validity of the scale. It concludes with a discussion of ethical issues that may be encountered, and guidelines for reporting the results of the scale development process. Appendices include a comprehensive guide to finding existing scales, and a brief introduction to exploratory and confirmatory factor analysis. It synthesizes the theory of scale construction with practical advice, making it the ultimate guide to how to develop and validate measurement scales that are to be used in the health sciences